Avaliação da ação antimicrobiana de medicações intracanais à base de produtos fitoterápicos associados a um veículo biologicamente ativo e sua influência na alteração de cor da estrutura dentinária - Palhano, Huriel Scartazzini (2017)
The aim of this study was to evaluate, in vitro, the antimicrobial activity of intracanal dressings composed by natural products associated to a biological active vehicle and its influence in color change of dentinal structure. To evaluate antimicrobial activity, eighty single rooted extracted human teeth were selected. The root canals were inoculated for 14 days with 100 µl of Enterococcus faecalis and, after this period, were randomly divided in 8 groups (n=10) according to different intracanal dressings: distilled water (DW) (negative control); 2% chlorhexidine gel (CHX) (positive control); calcium hydroxide; grape seed extract (GSE); and ginger extract (GE); the last three associated to distilled water or 2% chlorhexidine gel. The intracanal dressings remained into the root canals for 14 days. The decontamination evaluation of proposed treatments was performed by counting of colony forming units (CFUs), before and after 14 days of proposed treatments. Statistical analysis was performed by ANOVA, followed by Tukey’s post hoc procedure (α=0.05). For evaluation of change color, eighty dentin blocks were obtained from crowns of bovine teeth, remaining in contact with intracanal dressings described above during 14 days. The color measurement was performed before and after immersion of samples in the proposed treatments by digital spectrophotometry. Scores were obtained and submitted to statistical analysis by non-parametric Wilcoxon test (α=0.05). The highest ability to promote bacterial reduction was observed in groups 4 (GSE+DW), 6 (Ca(OH)2+CHX), 7 (GSE+CHX) and 8 (GE+CHX), with no statistical significant difference between them (p<0.05). Furthermore, it was possible to observe that after 14 days of treatment, the samples of groups 4 (GSE+DW) and 7 (GSE+CHX) have showed the highest medians of change color of dentinal structure, being these medians statistically higher to all other tested groups (p<0.05). The addition of 2% chlorhexidine gel improved the antimicrobial activity of intracanal dressings composed to natural products; however, these protocols induced significant change color in the dentinal structure.Key-words: calcium hydroxide, change color, chlorhexidine, Enterococcus faecalis, ginger extract, grape seed extract.